2020
DOI: 10.1002/ece3.6983
|View full text |Cite
|
Sign up to set email alerts
|

Foliar fungal endophyte community structure is independent of phylogenetic relatedness in an Asteraceae common garden

Abstract: Microorganisms have been intimately associated with macro-organisms for hundreds of millions of years (Krings et al., 2007; Ley et al., 2008). Research across plant and animal systems, combined with the advent of advanced sequencing technologies (Alivisatos et al., 2015), has revealed a wide range of taxonomic and functional diversity in their microbiomes (Christian et al., 2015). Despite the persistence and longevity of these symbioses over evolutionary timescales, the fact that most microbiota colonize hosts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
(131 reference statements)
1
6
0
Order By: Relevance
“…We did not find an effect of plant phylogenetic distance on endophyte community similarity, or v phylosymbiosis, but did find evidence for phylospecificity. Endophyte communities were structured with respect to plant species, families, and major groups, similar to past studies (Vincent et al 2016, Whitaker et al 2020. In particular, we found that endophytes within major groups of angiosperms (asterids, rosids, basal eudicots, and commelinids) associated with narrower phylogenetic breadths of plant species compared to endophytes within conifers and the one fern species.…”
Section: Plant Evolutionary Relatedness and Patterns Of Endophyte Host Specificitysupporting
confidence: 87%
See 2 more Smart Citations
“…We did not find an effect of plant phylogenetic distance on endophyte community similarity, or v phylosymbiosis, but did find evidence for phylospecificity. Endophyte communities were structured with respect to plant species, families, and major groups, similar to past studies (Vincent et al 2016, Whitaker et al 2020. In particular, we found that endophytes within major groups of angiosperms (asterids, rosids, basal eudicots, and commelinids) associated with narrower phylogenetic breadths of plant species compared to endophytes within conifers and the one fern species.…”
Section: Plant Evolutionary Relatedness and Patterns Of Endophyte Host Specificitysupporting
confidence: 87%
“…Phylospecificity (Poulin et al 2011, Cooper et al 2012, Huang et al 2014, Clark and Clegg 2017, or the tendency of symbionts to occupy more closely related hosts than expected by chance, shapes differences in endophyte communities that may not be correlated to plant phylogenetic distance. For example, Whitaker et al (2020) did not find evidence for phylosymbiosis because the genetic distances among 18 Asteraceae hosts were not correlated with endophyte community dissimilarity but did find evidence for phylospecificity, or a plant identity effect, where conspecific hosts tended to have more similar endophyte communities than heterospecific ones. Here, we tested for both phylosymbiosis, or the effect of phylogenetic distance on endophyte community dissimilarity, and phylospecificity, the non-random distribution of endophyte associations with respect to the plant phylogeny, to understand how endophyte host specificity varies with plant phylogenetic distance.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Many Asteraceae species are native to North America and have previously been shown to display a range of negative to positive PSFs (M€ unzbergov a and Surinov a 2015). Additionally, recent work has shown that Asteraceae leaf fungi vary by host species identity (Whitaker et al 2020) and that several Asteraceae experience negative PPFs (Whitaker et al 2017). All plant species tested here are native to the midwestern United States and span a range of functional strategies and phylogenetic distance.…”
Section: Study Systemmentioning
confidence: 97%
“…All plant litter inoculum was derived from a common garden (for more details, see Whitaker et al 2020) to ensure adequate biomass for litter inoculation and to isolate host species over environmental effects in the microbial communities. Briefly, the common garden was established in 2014 at the Indiana University Bayles Road Research and Teaching Preserve site in Bloomington, Indiana USA (39°13003.6″N, 86°32024.4″W).…”
Section: Inoculum Sourcementioning
confidence: 99%